Analysis of Factors Affecting Tobacco Export Volumes di Central Java Province Year 2010-2021 - Nurcahyani, Weni; Sharma, Abhishek (Sinergi International Journal of Management and Business, 2023)
This study discusses the price of tobacco and tobacco production on the volume of tobacco exports in Central Java Province in 2010-2021. This study aims to determine the effect of tobacco prices and tobacco production on the volume of tobacco exports in Central Java Province in 2010-2021. This research is aquantitative research with the subject of this research is Central Java Province. The data used comes from the Central Java Province Statistics Center in 2010-2021. The data analysis method used is a multiple linear regression analysis model using the EViews 12 program. The results of this study indicate that there is a positive and significant effect of tobacco production on the volume of tobacco exports in Central Java Province, and there is a negative and insignificant effect of tobacco prices on export volumes. tobacco in Central Java Province. And there is a positive and significant effect of price and production on the volume of tobacco exports in Central Java Province.